Spatial and temporal relationships between actin-filament nucleation, capping, and disassembly. - Iwasa, J.H.; Mullins, R.D. (Current Biology, 2007)
The leading actin network in motile cells is composed of two compartments, the lamellipod and the lamellum. Construction of the lamellipod requires a set of conserved proteins that form a biochemical cycle. The timing of this cycle and the roles of its components in determining actin network architecture in vivo, however, are not well understood.We performed fluorescent speckle microscopy on spreading Drosophila S2 cells by using labeled derivatives of actin, the Arp2/3 complex, capping protein, and tropomyosin. We find that capping protein and the Arp2/3 complex both incorporate at the cell edge but that capping protein dissociates after covering less than half the width of the lamellipod, whereas the Arp2/3 complex dissociates after crossing two thirds of the lamellipod. The lamellipodial actin network itself persists long after the loss of the Arp2/3 complex. Depletion of capping protein by RNAi results in the displacement of the Arp2/3 complex and disappearance of the lamellipod. In contrast, depletion of cofilin, slingshot, twinfilin, and tropomyosin, all factors that control the stability of actin filaments, dramatically expanded the lamellipod at the expense of the lamellum.The Arp2/3 complex is incorporated into the lamellipodial network at the cell edge but debranches well before the lamellipodial network itself is disassembled. Capping protein is required for the formation of a lamellipodial network but dissociates from the network precisely when filament disassembly is first detected. Cofilin, twinfilin, and tropomyosin appear to play no role in lamellipodial network assembly but function to limit its size.